Factors associated with knowledge, attitude and practice of caregivers on prevention of injuries among children in daycare centres in central Malaysia - Hassan, Nabiha Gul (2017)
Background: Childhood injuries have become one of the leading causes of morbidity and mortality among infants and pre-school children. With the increase in working mothers in the labour force, the demand for child care in the form of day-care centres has risen substantially in recent years. Young children cannot understand the risk of injury and thus do not know how to be safe. It is therefore essential that child-care settings provide a safe environment with qualified caregivers who are able to provide appropriate supervision. Objectives: To identify factors that affect the knowledge and attitudes on injury prevention of caregivers working in day-care centres in Putrajaya and Selangor. Methodology: A cross-sectional study was carried out among 399 participants in day-care centres in a total of 12 districts across Putrajaya and Selangor. Only licensed day-care centres were selected and approached for the study. Proportional to size random sampling method was used to collect information on socio-demographic, socio-economic factors of caregiver’s through the use of self-constructed, self-administered questionnaires. Data was analyzed using, descriptive, bivariate and multivariate data analysis by SPSS™ (version 21). The test used were Chi-square test, Logistic regression and Multiple Logistic Regression. Results: The study response rate was 89.47%. Only 38.6% of caregivers possessed good knowledge and 13.3% had good attitude on injury prevention. The majority of respondents were females (98.2%), Malays (35.6%), Muslims (48.6%) and between the age of 18-56 years. Majority of the participants were unmarried (51.4%), and did not have any children (70.9%). Majority of participants had at least a secondary education (51.6%) and earned at least minimum wage (56.4%). Most participants had completed the pre-requisite mandatory child care course (53.9%). Predictors of poor knowledge were participants who were below 25 years of age (AOR= 8.928, 95% CI 4.68 – 17.02, p = 0.001), single and unmarried (AOR= 2.077, 95% CI 1.13 – 3.83, p = 0.019), had secondary level education (AOR= 2.840, 95% CI 1.70 – 4.76, p = 0.001) and worked less than 60 hours per week (AOR= 1.967, 95% CI 1.15 – 3.33, p = 0.001). Predictors of poor attitude on injury prevention were participants who were below 25 years of age (AOR= 2.212, 95% CI 1.07 – 4.57, p = 0.032), earned minimum income (AOR= 2.331, 95% CI 1.11 – 4.91, p = 0.026) and had a secondary level education (AOR= 2.408, 95% CI 0.78 – 7.02, p = 0.013). Conclusion: In conclusion, results found that certain socio-demographic and socio-economic factors were associated with knowledge and attitude on injury prevention of caregivers. Results indicate that majority of caregivers working in Putrajaya and Selangor had poor knowledge and poor attitude on injury prevention. It should therefore be our utmost priority to ensure hiring qualified caregivers in order to reduce and eliminate the risk of future injuries among children in day-care centres.